2018
DOI: 10.1002/ajb2.1119
|View full text |Cite
|
Sign up to set email alerts
|

Bioclimatic factors at an intrabiome scale are more limiting than cyanobiont availability for the lichen‐forming genus Peltigera

Abstract: For these cyanolichens, factors driving patterns of symbiotic associations are scale dependent. Contrary to global-scale findings, generalist Peltigera species were not more widespread within the boreal biome than specialists. Nostoc availability was not the only driver of Peltigera species' geographic ranges; environmental factors also contributed to their intrabiome distributions. Climatic conditions (especially precipitation) limited the range of some Peltigera species more than the range of their cyanobact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 57 publications
1
33
1
Order By: Relevance
“…This not only provides a potential explanation for the maintenance of specialization by the mycobiont, but also the asymmetry of specificity in lichens, which is resulting from a gradual increase in generalism by broadly distributed Nostoc partners that are hosting an increasingly large number of Peltigera species sharing a most recent common ancestor. This is in agreement with the results from Lu et al (), where Peltigera species have narrower latitudinal ranges than their broadly distributed generalist Nostoc partners.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…This not only provides a potential explanation for the maintenance of specialization by the mycobiont, but also the asymmetry of specificity in lichens, which is resulting from a gradual increase in generalism by broadly distributed Nostoc partners that are hosting an increasingly large number of Peltigera species sharing a most recent common ancestor. This is in agreement with the results from Lu et al (), where Peltigera species have narrower latitudinal ranges than their broadly distributed generalist Nostoc partners.…”
Section: Discussionsupporting
confidence: 93%
“…If Peltigera species are not distributed randomly within our geographic regions, in a way that is linked to phylogeny, habitat partitioning may still be the underlying cause for part of the phylogenetically conserved partner selection observed in our system (Jüriado, Kaasalainen, Jylhä, & Rikkinen, ). For example, Lu et al () observed that along a latitudinal gradient crossing the entire boreal belt, some Peltigera species were restricted to specific portions of the gradient, well correlated to climatic variables such as total precipitation and mean temperature during the warmest quarter of the year. This study demonstrated that appropriate Nostoc phylogroup availability was not limiting for the Peltigera species sampled along this intra‐biome latitudinal gradient.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations